English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

the original equation is as follows:

S= 1/(1-dG) * 1/(1-tF)

thiis for exam revision so an answer as soon as.... please :D

2007-06-12 11:20:58 · 2 answers · asked by dj_toad2003 2 in Science & Mathematics Mathematics

2 answers

Since you don't specify whether "dG" and "tF" are two variables multiplied together, or something else, I'll assume they're two variables being multiplied.

Solving
S = 1 / (1-d*G)*1/(1-t*F)
for F yields the following:
F = (1 - S + d*G*S)/(d*G*t*S - t*S)

2007-06-12 11:31:05 · answer #1 · answered by lithiumdeuteride 7 · 0 0

ok
s*(1-dG)= 1/(1-tF)
so
1-tF = 1/ s*(1-dG)
-tF = [1/s*(1-dG)] - 1
multiply by -1/t
F=1/st(dG-1) + 1/t
or
F= 1/t [1/s(dG-1) +1]

2007-06-12 11:45:40 · answer #2 · answered by you_hgg 1 · 0 0

fedest.com, questions and answers